Simulation-based multiprofessional obstetric anaesthesia training conducted in situ versus off-site leads to similar individual and team outcomes: a randomised educational trial. Issue 10 (6th October 2015) - Sørensen, Jette Led; van der Vleuten, Cees; Rosthøj, Susanne; Østergaard, Doris; LeBlanc, Vicki; Johansen, Marianne; Ekelund, Kim; Starkopf, Liis; Lindschou, Jane; Gluud, Christian; Weikop, Pia; Ottesen, Bent
Abstract : Objective: To investigate the effect of in situ simulation (ISS) versus off-site simulation (OSS) on knowledge, patient safety attitude, stress, motivation, perceptions of simulation, team performance and organisational impact. Design: Investigator-initiated single-centre randomised superiority educational trial. Setting: Obstetrics and anaesthesiology departments, Rigshospitalet, University of Copenhagen, Denmark. Participants: 100 participants in teams of 10, comprising midwives, specialised midwives, auxiliary nurses, nurse anaesthetists, operating theatre nurses, and consultant doctors and trainees in obstetrics and anaesthesiology. Interventions: Two multiprofessional simulations (clinical management of an emergency caesarean section and a postpartum haemorrhage scenario) were conducted in teams of 10 in the ISS versus the OSS setting. Primary outcome: Knowledge assessed by a multiple choice question test. Exploratory outcomes: Individual outcomes: scores on the Safety Attitudes Questionnaire, stress measurements (State-Trait Anxiety Inventory, cognitive appraisal and salivary cortisol), Intrinsic Motivation Inventory and perceptions of simulations. Team outcome: video assessment of team performance. Organisational impact: suggestions for organisational changes. Results: The trial was conducted from April to June 2013. No differences between the two groups were found for the multiple choice question test, patient safety attitude, stress measurements, motivation or the evaluation of the simulations. The participants in the ISS group scored the authenticity of the simulation significantly higher than did the participants in the OSS group. Expert video assessment of team performance showed no differences between the ISS versus the OSS group. The ISS group provided more ideas and suggestions for changes at the organisational level. Conclusions: In this randomised trial, no significant differences were found regarding knowledge, patient safety attitude, motivation or stress measurements when comparing ISS versus OSS. Although participant perception of the authenticity of ISS versus OSS differed significantly, there were no differences in other outcomes between the groups except that the ISS group generated more suggestions for organisational changes. Trial registration number: NCT01792674.